Corruption as an Extraordinary Crime: A Historical and Legal Study in the Indonesian Legal System - Ahmad Baqi; Arya Farhan Azizi S. (AT-TAFAHUM: Journal of Law, 2024)
This paper aims to understand the history of corruption regulation through legal, historical, and international approaches. Corruption in Indonesian positive law is regulated by Law Number 31 of 1999 in conjunction with Law Number 20 of 2001, which covers various forms such as bribery, gratuities, and abuse of authority. In addition, an international perspective through the UNCAC and the views of experts emphasize that corruption is the abuse of power for personal gain. History shows that corrupt practices have existed since ancient civilizations and continue to develop into the modern era. In Indonesia, corruption regulations have developed from the colonial period, the Old Order, the New Order, to the reform era marked by the establishment of the Corruption Eradication Commission (KPK). Globally, the principles of transparency, accountability, and good governance are the main foundations for eradicating corruption. Thus, corruption regulations continue to develop in order to create a clean and integrated government.